Improving the Content of a Client-Server Technology Training Course: Set up and Collaborative Implementation of Local and Cloud-Based Remote Servers - Serik, Meruert; Mukhambetova, Meiramgul; Yeskermessuly, Alibek (International journal of emerging technologies in learning, 2019)
The integration of software solutions in the content of the training courses as a result of the socio-economic demand has a positive effect on the improvement of training the students for future professional activities. However, the latest achievements of hardware and software are not included in the content of the high education in a timely manner. Therefore, in our research we set the task to improve the content of the training course on the client-server technology using modern software capabilities. The content of the article consists of the conceptual structure of the training course, settings and integration of local and public cloud-based servers, describes the approaches of its using in the learning process. Microsoft SQL Server 2016, Microsoft Azure SQL Database, ASP.NET MVC 5 Framework were used as teaching environments. Training course was held for the students in the specialty of Computer Science of L.N.Gumilyov Eurasian National University and Kh.Dosmukhamedov Atyrau State University in Kazakhstan.